Evaluation words in advertising texts in Kazakh and English languages... (Eurasian Journal of Philology Science and Education, 2022)
The article deals with the peculiarities of the expression of evaluation words in Kazakh and English advertising texts in comparative ethnolinguistic and cognitive terms in order to determine their national-cultural connectivity. We evaluate the definition of good, bad, tasty, tasteless, outstanding, ugly and other properties of objects and phenomena. Evaluation is carried out through the human value system, but it differs from value in its negative form, which is directly related to the nature of the object and phenomenon. In determining the place of evaluative words in advertising in Kazakh and English, we understand advertising materials as a currently widely used type of text in which evaluative words act as the main means of influencing the consumer to meet their needs. The meaning of evaluation is closely connected with the theoretical and applied spheres of language. This versatility is determined by a comprehensive study of issues related to the relationship between language and speech, typology and structure of lexical meaning, lexical expressiveness, and emotional and pragmatic aspects. In this article advertising texts in two languages have been selected, and the similarities and peculiarities of the semantic meaning of the evaluation words they contain have been revealed. Since advertisements have a supplier and a consumer, evaluation words play a major role in establishing the relationship between them.